La corte en la historiografía modernista española. Estado de la cuestión y bibliografía - Vázquez Gestal, Pablo (Cuadernos de Historia Moderna, 2003)
This article is divided in two main parts: the first aims to familiarize the reader with the circumstances and historiographic characteristics that surround the birth and development of the study dedicated to the court sphere in the Spanish historiography, considering however the debates have been caused by the last modern historiography. In the second, a bibliographical selection with the main titles of the Spanish tradition regarding the Court studies is given.